(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper presents a comparative analysis of Jean Rhys’ Wide Sargasso Sea and Bessie Head’s Maru. It explores the identity problem confronted by both heroines, Antoinette of Wide Sargasso Sea and Margaret of Maru, and their fight in a culture that is triple separated by race, class and gender to solve this problem. It discusses Antoinette and Margaret’s distinctions and parallels in their desire for and fight for an independent identity, and investigates how effective they are or fail to articulate their identities. Through taking up comparative literature strategies and approaches, postcolonial theory and feminist theory, the paper examines the two novels, stressing external influences, which may help, disrupt and prevent the tough and long seek for identity and independence by the two heroines. The study explores the underlying parallels and distinctions in the handling of the issue of identity by the two protagonists and how the female character fought to reach her ambition in each work.